Tenecteplase versus Alteplase or Standard Care for Improving Functional Outcomes in Acute Ischaemic Stroke: A Systematic Review and Meta-Analysis - Steffanny Regina Maria Andini; Praise Angelny Agnes Manoppo (Sriwijaya Journal of Neurology, 2026)
Introduction: Intravenous alteplase is the standard fibrinolytic for acute ischaemic stroke, but tenecteplase offers practical advantages as a single-bolus alternative. This systematic review and meta-analysis aimed to consolidate recent randomised controlled trial (RCT) evidence on the effectiveness of tenecteplase for improving functional outcomes, with explicit attention to dose stratification. Methods: Following the PRISMA 2020 framework, we searched PubMed for RCTs published between January 2017 and May 2026 comparing tenecteplase with alteplase or standard care. The primary efficacy outcome was an excellent functional outcome at 90 days (modified Rankin Scale 0–1). Trial-level effects were harmonised on a standardised mean-difference scale (Hedges g) and pooled using a DerSimonian–Laird random-effects model. Pre-specified subgroup analyses examined dose (0.25 vs 0.40 mg/kg). Results: Ten RCTs (n=7,118) met eligibility, and eight contributed dichotomous data to the quantitative synthesis. The pooled Hedges g was 0.063 (95% CI –0.067 to 0.192; p=0.344) with substantial heterogeneity (I²=77.1%). Tenecteplase 0.25 mg/kg produced a small but statistically significant favourable effect (Hedges g 0.108; 95% CI 0.0001 to 0.215), whereas the 0.40 mg/kg dose was directionally inferior. Excluding the prematurely terminated NOR-TEST 2 Part A trial yielded a pooled Hedges g of 0.088 (p=0.029) and reduced heterogeneity (I²=39.7%). Conclusion: Intravenous tenecteplase performed at least as well as alteplase or standard medical care for 90-day functional recovery, with the most favourable signal confined to the 0.25 mg/kg dose. The findings supported the integration of tenecteplase 0.25 mg/kg into standard acute neurology pathways, particularly where bolus administration simplified workflow.